2009
DOI: 10.1038/sc.2008.178
|View full text |Cite
|
Sign up to set email alerts
|

Properties and outcomes of spinal rehabilitation units in four countries

Abstract: Objective: Compare rehabilitation after spinal cord lesions (SCL) in different countries. Design: Multicenter comparative study. Setting: Four spinal rehabilitation units, in Denmark, Russia, Lithuania and Israel. Subjects: 199 SCL patients. Interventions: Information was collected about unit properties, rehabilitation objectives, American Spinal Injury Association (ASIA) scale and spinal cord independence measure (SCIM) assessments, and patient data. w 2 -test, t-test, ANOVA and ANCOVA were used for statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…Ackerman et al 6 showed similar results compared with the present investigation, reporting that tetraplegic patients experienced a mean increase in the outcome-score by 6.3 points, whereas patients with paraplegia experienced a mean increase of 5.75 points. A multicenter study of Fromovich-Amit et al 14 showed that the beginning and length of rehabilitation is important for the outcome of SCI patients. It was shown that patients with a moderately delayed rehabilitation needed a longer rehabilitation than those with a shorter period until rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Ackerman et al 6 showed similar results compared with the present investigation, reporting that tetraplegic patients experienced a mean increase in the outcome-score by 6.3 points, whereas patients with paraplegia experienced a mean increase of 5.75 points. A multicenter study of Fromovich-Amit et al 14 showed that the beginning and length of rehabilitation is important for the outcome of SCI patients. It was shown that patients with a moderately delayed rehabilitation needed a longer rehabilitation than those with a shorter period until rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Such an instrument may resemble the combination of lesion level and American Spinal Injury Association impairment scale (AIS) grade, which describes briefly the neurological status and provides abundant information on neurological deficit, its distribution and its prognosis. 1 A similarly concise description of function after SCL may not be feasible because of the large number of possible combinations of task scores. But these combinations are not random, and patterns can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, for a group of patients with paraplegia injured in 2000-2004, mean rehabilitation LOS was 116 days. 4 In four European countries, rehabilitation LOS in recent years, across all neurological categories of injury, ranged from 47 days in Russia 5 to 240 days in the Netherlands, 6 with 177 days in Denmark 5 and 122 days in Italy. 7 In contrast to the many available citations on overall LOS for SCI rehabilitation admissions, published information on the type and extent of services delivered during rehabilitation is scant.…”
Section: Introductionmentioning
confidence: 99%